2022
DOI: 10.1186/s12950-022-00300-3
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA circFADS2 is under-expressed in sepsis and protects lung cells from LPS-induced apoptosis by downregulating miR-133a

Abstract: Background It has been reported that hsa_circRNA_100833 (identified as circFADS2) and miR-133a play opposite roles in LPS-induced cell apoptosis, which contributes to the development of sepsis. This study was carried out to explore the interaction between circFADS2 and miR-133a in sepsis. Methods Expression of circFADS2 and miR-133a in plasma from both sepsis patients (n=62) and healthy controls (n=62) was studied by RT-qPCR. Pearson’s correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…At present, increasingly, reports have confirmed that circRNAs could act as ceRNAs to sponge miRNAs and ultimately regulate the expression of target genes (23). Meanwhile, circRNAs have been manifested to mediate SA-ALI progression by binding miRNAs (24). The abundance of miR-940 was identified to be declined in sepsis patients and cecal ligation-perforation-stimulated sepsis animal models, and overexpression of miR-940 alleviated injury and inflammatory processes in sepsis models (25).…”
Section: Discussionmentioning
confidence: 99%
“…At present, increasingly, reports have confirmed that circRNAs could act as ceRNAs to sponge miRNAs and ultimately regulate the expression of target genes (23). Meanwhile, circRNAs have been manifested to mediate SA-ALI progression by binding miRNAs (24). The abundance of miR-940 was identified to be declined in sepsis patients and cecal ligation-perforation-stimulated sepsis animal models, and overexpression of miR-940 alleviated injury and inflammatory processes in sepsis models (25).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the increased production of miR-133a in the inflammatory adipose tissues, ovaries of obese and LPS-treated mice, and LPS-treated granulosa cells indicated that increased expression of miR-133a is associated with inflammatory status. Accordingly, in two recent clinical studies, high miR-133a levels were found in the serum of sepsis patients and LPS-treated human bronchial epithelial cells [ 45 , 46 ] . Therefore, HFD induced the hypertrophy of adipose cells and the proinflammatory polarization state of macrophages, which led to the release of several inflammatory cytokines and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Genomics of sepsis hint that patients present inflammation and immunosuppression with altered expression levels of most genes 5 . In addition, some molecular players have been identified to be potential targets for the treatment of organ failure in patients with sepsis, such as microRNAs (miRNAs) and circular RNAs (circRNAs) 6 . These transcripts have also been illustrated to be related to the pathogenesis of multiple organ system failures 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, circRNAs can regulate a variety of molecular mechanisms, including inflammation and immune responses, as well as a variety of biological processes in various metabolic organs 11 . For example, altering circ-fatty acid desaturase 2 or circ_0001679 at the gene level can inhibit sepsis-induced ALI progression 6,12 . CircRNA protein tyrosine kinase 2 (circPTK2) has attracted academic attention in the aspect of malignancy [13][14][15] and has also been studied to mediate Circular RNA protein tyrosine kinase 2 aggravates pyroptosis and inflammation in septic lung tissue by promoting microRNA-766/ eukaryotic initiation factor 5A axis-mediated ATP efflux apoptosis and inflammatory response in sepsis-induced myocardial injury 16 .…”
Section: Introductionmentioning
confidence: 99%